Importance of Effective Teaching methods in Demography: A Philosophical Review - Dulal, Tulasa Devi (Nepal Population Journal, 2026)
The paper discusses the teaching method of demography and critiques traditional teaching methods in Nepali formal institutions, arguing that they are no longer effective due to increased accessibility of knowledge. The paper is based on secondary data. It used meta analysis of reports, historical documents, statistics, and theories. Teaching in demography involves a blend of theoretical understanding, practical application, and critical thinking. Key teaching methods include a theoretical foundation, practical application, problem-solving, active learning, data analysis, GIS application, integration of formal and substantive demography, critical thinking, inquiry-based learning, technology use, values clarification, experiential learning, cooperative learning, and project-based learning. These methods encourage active participation, critical thinking, and exploration of real-world issues using demographic data and models. Teachers can establish a dynamic learning environment that promotes a greater comprehension of demography and its global importance by implementing these strategies.